2010
DOI: 10.1093/ndt/gfq708
|View full text |Cite
|
Sign up to set email alerts
|

Mindin: a novel marker for podocyte injury in diabetic nephropathy

Abstract: Mindin could be related to podocyte injury and appears to be an early biomarker of the progression of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
2
37
1
1
Order By: Relevance
“…In this analysis, we focused on mindin (also called spondin 2, SPON2 ) as a possible biomarker for several reasons [30,31]. Mindin protein expression levels in the glomeruli of KK mice were significantly upregulated with the progression of DN, they were mainly localized in podocytes by immunohistochemical staining and were a secreted protein.…”
Section: New Biomarkersmentioning
confidence: 99%
“…In this analysis, we focused on mindin (also called spondin 2, SPON2 ) as a possible biomarker for several reasons [30,31]. Mindin protein expression levels in the glomeruli of KK mice were significantly upregulated with the progression of DN, they were mainly localized in podocytes by immunohistochemical staining and were a secreted protein.…”
Section: New Biomarkersmentioning
confidence: 99%
“…At the end of all these processes, increase in mesangial matrix, thickening of basement membrane and podocyte injury occur. Recent studies have indicated that podocyte injury is a hallmark of the mechanisms in the pathogenesis of glomerular disease and DN . Inflammatory and immune response mechanisms may also play a key role.…”
mentioning
confidence: 99%
“…To answer these questions, we established KK/Ta mice expressing human adiponectin in the liver. The KK/Ta mouse is an animal model of metabolic syndrome exhibiting moderate obesity with excessive visceral fat accumulation, hyperinsulinemia, dyslipidemia and hyperglycemia (Liao et al 2003, Tanimoto et al 2004, Akagiri et al 2008, Murakoshi et al 2010. Here, we showed that hyperadiponectinemia prolonged the lifespan of this murine model of metabolic syndrome without affecting body weight by attenuating AKT signaling and chronic low-grade inflammation.…”
Section: Introductionmentioning
confidence: 61%